Variable Presentation and Reduced Penetrance in Autosomal Dominant Acute Necrotizing Encephalopathy Related to RANBP2 Variant - Carvalho, Daniel R.; Speck-Martins, Carlos E.; Martins, Bernardo J. A. F.; Izumi, Ana Paula; La Rocque-Ferreira, Alessandra (Journal of Pediatric Genetics, 2021)
Acute necrotizing encephalopathy (ANE) is clinically characterized by fever, acute alteration of consciousness, seizures, and rapid progression to coma within days of onset of a viral illness occurring in healthy children without evidence of central nervous system infection. Brain magnetic resonance imaging (MRI) shows multiple symmetrical lesions affecting primarily the thalami but also brain stem, putamina, periventricular white matter, and cerebellum. Most cases of ANE are sporadic and nonrecurrent. However, a missense variant in RANBP2 has been identified in some families with recurrent ANE (OMIM # 608033), also named autosomal dominant ANE (ADANE). Clinical manifestation, clinical course, and brain MRI imaging findings of six affected members of two distinct families with ADANE were described. Sequencing revealed heterozygous c.1754C > T variant in RANBP2 (p.Thr585Met) in affected and asymptomatic family members. Only few ADANE families have been reported and it is the first description in South America. Differential diagnosis of Leigh disease and acute disseminated encephalomyelitis is discussed. Our report reinforces incomplete penetrance of ADANE and intrafamilial phenotypic variability of outcome.
Keywords: acute necrotizing encephalopathy; RANBP2; autosomal dominant; acute disseminated encephalomyelitis (ADEM)